Neoliberalism, anti-politics and political crisis in Peru - Romero Reyes, Antonio (2018)
The article seeks to understand and unravel the historical nature of anti-politics in relation to neoliberalism and the context of the crisis of politics in our country. A review is made of the historical and theoretical framework of the subject, revising texts by Degregori, Lynch and other Latin American authors, focusing on the party crisis and the political economy of anti-politics. The conclusions are tentative in the sense that these are tentative answers to the following questions: How to end anti-politics? Democratizing democracy or refunding the country?